2020
DOI: 10.1111/saje.12275
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Distributional Impact of COVID‐19: Evidence from Macro‐Micro Modelling of the South African Economy

Abstract: A computable general equilibrium model linked to a microsimulation model is applied to assess the potential short‐term effects on the South African economy of the ongoing COVID‐19 pandemic. With a particular focus on distributional outcomes, two simulations are run, a mild and a severe scenario. The findings show significant evidence of decline in economic growth and employment, with the decline harsher for the severe scenario. The microeconomic results show that the pandemic moves the income distribution curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 14 publications
3
22
0
2
Order By: Relevance
“…These studies suggested that poverty alleviation benefited from the growth of agricultural production and productivity, increased agricultural investment, appropriate amount and method of fertilizers application. In addition, around 9% of existing studies accounted for progress evaluation and interactions between SDGs (Allen et al, 2017;Allen et al, 2021), assessing the influence of various factors on poverty including health policies (Shrime et al, 2016), disease spread (Chitiga-Mabugu et al, 2021), technical efficiency (Islam and Haider, 2018), population aging (X. Wang et al, 2017), and urban characteristics (Duque et al, 2015).…”
Section: Bibliometric Informationmentioning
confidence: 99%
“…These studies suggested that poverty alleviation benefited from the growth of agricultural production and productivity, increased agricultural investment, appropriate amount and method of fertilizers application. In addition, around 9% of existing studies accounted for progress evaluation and interactions between SDGs (Allen et al, 2017;Allen et al, 2021), assessing the influence of various factors on poverty including health policies (Shrime et al, 2016), disease spread (Chitiga-Mabugu et al, 2021), technical efficiency (Islam and Haider, 2018), population aging (X. Wang et al, 2017), and urban characteristics (Duque et al, 2015).…”
Section: Bibliometric Informationmentioning
confidence: 99%
“…It is also similar to the Klaten and Wonogiri markets, reducing turnover (AZIMAH et al, 2020). In the global context, there was a tremendous economic distraction (Kusno, 2020), which damaged the international market (Ashraf, 2020)which resulted in a significant reduction in employment (Chitiga-Mabugu, Henseler, Mabugu, & Maisonnave, 2020). Unlike previous studies, this study presents a different perspective because it specifically looks at the direct impact of Covid-19 on female workers in Serang City.…”
mentioning
confidence: 94%
“…Also, the ravaging impact of the pandemic is still ongoing, and one cannot predict the fate of Saudi Arabia with this new variant known as Delta Plus. Evidence shows that there are other possible ways through which the pandemic feeds into other parts of the economy (Chitiga-Mabugu et al, 2021). This makes economic modelling activities difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this paper will emphasise the outcomes of the COVID-19 on the economy and households of the KSA people. Though there are few papers in this direction of recent, such as Maliszewska et al (2020), Laborde et al (2020) and Chitiga-Mabugu et al (2021), but not in KSA. The authors traced the effects of the COVID-19 on the economy through some selected outlets.…”
Section: Introductionmentioning
confidence: 99%